Predicting Gen Z Mangrove Conservation Awareness on Instagram: A Community Account Study of Campaign Exposure and Ambassador Credibility in Indonesia - Paundra Hanutama; Sulthan Rafi Abyan Hidayat; Meilannie Louise Hajo; Aditi Jadhav (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2026)
This study measures the role of Instagram as an environmental communication space for Generation Z in Indonesia. Grounded in the frameworks of Environmental Communication and Social Influence Theory, this study positions the variables of community-based digital campaign exposure (